8-pointed pavilion / Nurul Aimi Aliah Razman ... [et al.] - Razman, Nurul Aimi Aliah; Khairul Azmi, Nur Khairunnisaa’; Abd Aziz, Ruzana; Haron, Siti Norsazlina (2024)
This pavilion project was built as an outcome of an undergraduate design studio at University Technology MARA (UiTM) Seri Iskandar. The pavilion draws inspiration from the 8-pointed star geometry, a unique element in Islamic architecture. This architectural choice holds profound cultural and symbolic significance in Islamic tradition. The 8-pointed star symbolises unity, harmony, and stability, reflecting the principles of balance and togetherness. Islamic art and geometric patterns heavily influence the towers' aesthetics. After conducting research and study, we decided to develop and construct the 8-Pointed Pavilion, which embodies the purity of Islam. In this project, we design the pavilion using geometric shapes and Islamic patterns, incorporating both the furniture's shape and the interior and exterior of the pavilion. These patterns not only showcase the artistry of the craftsmen, but also demonstrate their exceptional skills and comprehension of Islamic geometry. Sustainable design is the top priority when constructing a building or pavilion to create a comfortable and welcoming space for everyone. This includes creating a comfortable and pleasant interior climate through natural ventilation and natural light, as well as reducing energy consumption. We placed a mini garden at various corners and in the centre of the building to create a sense of harmony that aligns with the purity of the Islamic concept. Geometry and islamic pattern, modern technology, natural light and ventilation, purity of islamic concept, sustainable design